Why do Pre-service English Teachers Choose Teaching?: An Analysis of Motivational Factors at English Education Study Program of Sriwijaya University - Aprilia, Resti; Pitaloka, Nova Lingga (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study looks at what motivates pre-service English teachers at Sriwijaya University. It also examines if gender and semester level affect their motivation. Using the FIT-Choice framework, researchers collected data from 144 students with a questionnaire adapted from Kilinc et al. (2012) and Topkaya & Uztosun (2013). The questionnaire covered twelve motivational factors. The findings show that students are mainly driven by altruistic values. They want to make a social contribution, shape children’s futures, and promote social fairness. Female students had notably higher motivation scores than male students, especially regarding intrinsic value, shaping children’s future, and prior teaching experiences. However, there were no significant motivational differences across semester levels. These results highlight the need to focus on motivational factors in teacher education programs. This focus can help strengthen student commitment and readiness for the teaching profession.